Plant productivity and biological yield of winter wheat grain under the influence of morpho-regulators on different mineral nutrition backgrounds (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The results of two years of research on the effect of morphoregulators in combination with different mineral nutrition backgrounds on the formation of plant productivity and biological yield of winter wheat grain are presented.Formulation of the problem. The effectiveness and practical application of combinations of various agrochemicals, in particular different forms of mineral fertilizers and morphoregulators, remain insufficiently studied. In addition, new types and formulations of fertilizers and morphoregulators are systematically appearing on the market, and new varieties of winter wheat are being introduced into production, which differ in their morpho-biotype and, therefore, may react differently to elements of cultivation technology, in particular, the system of nutrition and plant growth regulation. In addition, growing weather conditions are changing, in particular, there is a gradual increase in temperature and a decrease in precipitation. All these factors indicate the advisability of conducting research aimed at more efficient use of mineral fertilizers and morphoregulators in different growing regions.The purpose of the research. The aim of the research was to determine and compare the effectiveness of modern morphoregulators with different bases in combination with different mineral nutrition backgrounds on the formation of plant productivity elements and biological yield of winter wheat grain in the conditions of the eastern Forest-Steppe of Ukraine.Research methods. The research was conducted in 2024 and 2025 on the basis of grain-row crop rotation at the Department of Plant Growing of the State Biotechnological University. The effectiveness of using morphoregulators in combination with different mineral nutrition backgrounds was studied on Bogdana, a widely used, medium-maturing, intensive type of soft winter wheat.A two-factors experiment was set up using the split-plot method in three replicates in a single layer. The first-order plots were four mineral nutrition backgrounds: 1 – control; 2 – top dressing with N15P30K20 (150 kg/ha of MACROSTAR -N9P20K12) + top dressing after physical ripeness of the soil (22-23rd microphase) with urea at a rate of N35 + + foliar feeding with urea at a dose of 22 kg/ha (N10) during the 37th microphase; 3 and 4 – same as the second option, but the urea application rate during the 22-23rd microphase is increased to 108 and 141 kg/ha (N50 and N65), respectively. The second order plots consisted of five options for treating crops with retardant morphoregulators during the 31st microphase according to the BBCH classification: I – control (without morphoregulators); II – Moddus Star (0.3 l/ha); III – Retacel (1.5 l/ha); IV – Medax TOP (0.7 l/ha); V – mixture of Moddus Star (0.2 l/ha) + Retacel (1.0 l/ha).  The area of the experimental plot was 37.5 m2, and the accounting area was 30 m2.Research results. It has been established that it is possible to form higher elements of plant productivity, as well as significantly increase the biological yield of winter wheat grain through the use of morphoregulators on different nutritional backgrounds.The highest number of plants and lateral productive stems of winter wheat was 329 and 276 respectively, was observed in 2025 in the variant of treating crops with the Medax TOP regulator against the background of applying the highest dose of nitrogen (N65) during the 22-23rd microphase according to the BBCH classification. In fact, the same indicators – 327 plants and 278 lateral productive stems – were observed in the variant of applying this regulator against the background of a lower dose of nitrogen – N50.The greatest changes in the number of wheat plants before harvesting were influenced by the studied variants of the nutrition system, while the number of lateral productive stems was influenced by weather conditions. Thus, the range of variation in the number of plants under the influence of morphoregulators and weather conditions was 2.8 % and 4.1 %, respectively, while under the influence of the nutrition system it was  7.1 %. The range of variation in the number of lateral productive stems under the influence of morphoregulators and the nutrient background was 5.9 % and 11.4 %, respectively, while under the influence of weather conditions it was 34.2 %.The largest number and weight of grains from the main and side stems were formed in the variants treated with the Medax TOP regulator against the background of nitrogen fertilization during the 22-23rd microphase at a dose of N50. Increasing the nitrogen dose to N65 did not provide a significant increase in these indicators.Among the regulators studied, both in terms of their effect on plant productivity and in terms of their effect on the biological grain yield of the main and lateral stem systems of winter wheat, the product Medax TOP was the best. Crops treated with this product formed significantly higher biological grain yield of both stem systems in the weather conditions of both years on all studied mineral nutrition backgrounds.The highest overall biological yield of winter wheat was achieved in the treatment variant during the 31st microphase according to the BBCH classification with the Medax TOP regulator against the background of the highest nitrogen application rate (N65) during the 22nd-23rd microphase – 5.06 t/ha in 2024 and 6.87 t/ha in 2025. At the same time, virtually the same indicators were obtained for N50 application – 5.01 and 6.78 t/ha, respectively. Therefore, given the lack of a significant difference in biological grain yield between these options, it is not advisable to increase the nitrogen dose from 50 to 65 kg/ha.Conclusions. No significant difference in terms of overall biological grain yield was found between the options of treating crops with the Medax TOP regulator and a mixture of Moddus Star and Retacel 720 products. However, preference should be given to the application of the Medax TOP regulator because, firstly, the biological yield when using it was higher, albeit insignificantly, secondly, the spraying process is simplified because only one product is applied, and thirdly, the Medax TOP regulator has a wider temperature range of effective operation.
Keywords: winter wheat; fertilizers; growth regulator; nutrition system; productivity elements; plant density; biological yield